2015
DOI: 10.1088/1742-6596/582/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of compression strength of high performance concrete using artificial neural networks

Abstract: Abstract. High-strength concrete is undoubtedly one of the most innovative materials in construction. Its manufacture is simple and is carried out starting from essential components (water, cement, fine and aggregates) and a number of additives. Their proportions have a high influence on the final strength of the product. This relations do not seem to follow a mathematical formula and yet their knowledge is crucial to optimize the quantities of raw materials used in the manufacture of concrete. Of all mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 13 publications
0
10
0
2
Order By: Relevance
“…El resultado es superior al obtenido por [10] en su estudio de los intervalos de confianza de las predicciones en los mercados de energía en el cual se obtuvieron PICP(%) entre 92.6 y 94.1%. El resultado obtenido es también superior al obtenido por [28] en su estudio de los intervalos de confianza de las predicciones de demanda del mercado eléctrico, los cuáles obtuvieron PICP(%) entre el 50% y el 100%.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…El resultado es superior al obtenido por [10] en su estudio de los intervalos de confianza de las predicciones en los mercados de energía en el cual se obtuvieron PICP(%) entre 92.6 y 94.1%. El resultado obtenido es también superior al obtenido por [28] en su estudio de los intervalos de confianza de las predicciones de demanda del mercado eléctrico, los cuáles obtuvieron PICP(%) entre el 50% y el 100%.…”
Section: Discussionunclassified
“…Los ensayos de compresión axial se realizaron en una máquina TONI-TECHNIK provista de una célula de 3.000KN y TINIUS OLSEN DE 1.500KN. De acuerdo a estudios similares realizados anteriormente [10][11][12]. Como variables explicativas se tomaron el tiempo de curado, tipo cantidad y porcentaje de aditivo; tipo, porcentaje y cantidad de microsílice; cantidades de agua, piedra, arena y cemento; el TNM de la piedra, los pesos específicos de la arena y la piedra y la relación agua-cemento.…”
Section: Concreto De Alta Resistenciaunclassified
“…Their ANN model was able to predict experimental results accurately. Torre et al (2015) also constructed a multilayer perceptron model to predict compressive strength of high-performance concrete. The model accurately predicted the compressive strength of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The application of artificial neural networks (ANNs) for prediction and optimization of concrete properties is relatively a new research area and recent studies have demonstrated that ANN is one of the best machine learning tools for this purpose (Chopra et al., 2015; Muthupriya et al., 2011; Torre et al., 2015). The comparison between ANN and some classical modeling techniques such as response surface methodology (RSM), Plackett-Burman designs, full factorial designs and randomized block designs showed the supremacy of ANN as a modeling technique in analyzing non-linear relationships of data sets, which consequently provides good fitting for data and as well as better predictive ability (Hacene et al., 2013).…”
Section: Introductionmentioning
confidence: 99%